Mitochondrial DNA sequence variation and haplogroup distribution in Chinese patients with LHON and m.14484T>C. - Dandan Yu (Public Library of Science (PLoS), 2010)
Background Leber hereditary optic neuropathy (LHON, MIM 535000) is one of the most common mitochondrial genetic disorders caused by three primary mtDNA mutations (m.3460G>A, m.11778G>A and m. 14484T>C). The clinical expression of LHON is affected by many additional factors, e.g. mtDNA background, nuclear genes, and environmental factors. Hitherto, there is no comprehensive study of Chinese LHON patients with m.14484T>C. Methodology/principal findings In this study, we analyzed the mtDNA sequence variations and haplogroup distribution pattern of the largest number of Chinese LHON patients with m.14484T>C to date. We first determined the complete mtDNA sequences in eleven LHON probands with m.14484T>C, to discern the potentially pathogenic mutations that co-segregate with m.14484T>C. We then dissected the matrilineal structure of 52 patients with m.14484T>C (including 14 from unrelated families and 38 sporadic cases) and compared it with the reported Han Chinese from general populations. Complete mtDNA sequencing showed that the eleven matrilines belonged to nine haplogroups including Y2, C4a, M8a, M10a1a, G1a1, G2a1, G2b2, D5a2a1, and D5c. We did not identify putatively pathogenic mutation that was co-segregated with m.14484T>C in these lineages based on the evolutionary analysis. Compared with the reported Han Chinese from general populations, the LHON patients with m.14484T>C had significantly higher frequency of haplogroups C, G, M10, and Y, but a lower frequency of haplogroup F. Intriguingly, we also observed a lower prevalence of F lineages in LHON subjects with m.11778G>A in our previous study, suggesting that this haplogroup may enact similar role during the onset of LHON in the presence of m.14484T>C or m.11778G>A. Conclusions/significance Our current study provided a comprehensive profile regarding the mtDNA variation and background of Chinese patients with LHON and m.14484T>C. Matrilineal background might affect the expression of LHON in Chinese patients with m.14484T>C.